Statistical study on the conjugacy of geomagnetic field variations - Kumiko Hashimoto; Natsuo Sato; Masahiko Kusunose (National Institute of Polar Research, 1993)
The diurnal and seasonal dependence of the conjugacy of geomagnetic variations associated with the auroral electrojet is investigated and their dependence on ionospheric conductivity (due to solar EUV and auroral particle precipitations) is examined. We analyze the fluxgate magnetometer data from two magnetic conjugate stations at Syowa in Antarctica and at Aedey in Iceland, during the period from September 1989 to September 1990. Here, a magnitude of geomagnetic variation is defined as a deviation from quiet time geomagnetic elements for each month. We further examined a ratio of the magnitudes of the geomagnetic variations between two stations (ΔHSYOWA/ΔHAEDEY). Principal characteristics of the magnitude ratio between two conjugate observatories include the following : When the sense of magnetic variations of H component is positive (northward), the magnitude in the summer hemisphere is about three times larger than that in the winter hemisphere during 1300-2000 UT, and the magnitude ratio becomes largest around 1800 UT in the northern summer. Almost the same magnitude of geomagnetic variations at the two observatories appeared at around 1800 UT in February and October. On the other hand, for negative variation (southward), a similar seasonal change can be seen only under low magnetic activity conditions. The magnitude ratio for the negative variation is always smaller than that for the positive one. The ratios are equal around 0600 UT in April and August. The magnitude of geomagnetic variation showed dependence on the geomagnetic activity level. Generally, in all seasons, the magnitude at Syowa shows to be larger than that at Aedey relatively for both positive and negative variations with geomagnetic activity level. These results are consistent with the diurnal and seasonal change of the ionospheres depending on the sunlit conditions. We further examined the effects of ionization made by auroral particle precipitations.